Toroidal quarter waves in the Earth’s magnetosphere: observational perspective - Bulusu, Jayashree; Sinha, A.K.; Vichare, Geeta (My University, 2015)
Quarter waves in the Earth’s magnetosphere are standing Alfvén waves excited on geomagnetic field lines when the conjugate ionospheres display strong asymmetry in conductivity. In this paper, we have examined the characteristics of these waves by analyzing two years (2007–2008) of magnetometer data from the geostationary satellite GOES-11. These waves are predominantly identified during quiet geomagnetic conditions based on interhemispheric conductivity contrast and opposite signs of wave reflection coefficients at the conjugate ionospheres. The observed frequencies are used in a numerical model to compute the equatorial ion density by assuming that the plasma consists only of protons at geostationary height during quiet conditions. The number density of protons thus obtained is compared with an empirical model. The phase difference between the waves observed at the satellite and northern conjugate ground station is in accord with model expectations for quarter mode waves. We also for the first time report the occurrence of an event depicting harmonically structured quarter wave oscillations. Statistical analysis of the seasonal and MLT (Magnetic local time) dependence of these oscillations shows that they mostly occur during solstices and around terminators (i.e. dawn and dusk time). In addition, it is observed that occurrence is more prevalent during dawn in the June solstice and dusk during the December solstice.
Keywords: Geomagnetic pulsations; ULF waves; Field line oscillations; Quarter waves; Earth’s magnetosphere; Alfvén waves